Palladium‐Catalyzed Annulation of Acyl Fluorides with Norbornene via Decarbonylation and CO Reinsertion. Issue 57 (7th September 2020) - Sakurai, Yuka; Ogiwara, Yohei; Sakai, Norio
Abstract: A palladium‐catalyzed annulation of acyl fluorides with norbornene is described. This study reports the first example of an annulation of acyl fluorides in the presence of a transition‐metal catalyst. Polycyclic ketones are obtained from the cleavage of the C−F and C−H bonds of the acyl fluoride and the rearrangement of the carbonyl moiety by decarbonylation and CO reinsertion. Abstract : A Pd‐catalyzed annulation of acyl fluorides with norbornene via C−F and ortho C−H bond cleavage has been developed. The reaction proceeds via the rearrangement of CO and provides the corresponding polycyclic ketones in good to excellent yield.